Computer based ultrasonic system for mechanical and acoustical characterization of materials - Rosly Jaafar, 1955-; Mohd. Rozni Mohd. Yusof; Md. Supar Rohani; Rashdi Shah Ahmad; Amirudin Shaari; Khaidzir Hamzah; National Seminar on Non-Destructive Testing : Facing The Challenges of 21st. Century (2001 : Universiti Tenaga Nasional, Bangi) (Skudai : Universiti Teknologi Malaysia, 2001)
40